Psychographic Profiles Of Consumers And Purchase Intention Of Environmentally Safe Products In Penang - Ooi, Phei Lin (2014)
This study investigates the predicting variables that induce the purchase intention of environmentally safe products in psychographic perspective. The predictive variables encompass lifestyle, interest, value, knowledge and perception, attitude of consumers towards environment and past consumption experience. The survey result are analyzed using data collected from consumers in Penang using Structural Equation Modelling. The results exhibited that the psychographic variables proponed for assessment are related to the attitude of consumers towards environment. The attitude of consumers demonstrates positive relationship with purchase intention of environmentally safe products. The psychographic variables also manifested relationship with purchase intention through the mediating variable, attitude of consumers towards environment. Attitude of consumers towards environment that are favourable are vital for the purchase intention of environmentally safe products. The distinctive psychographic characterictics of consumers are influencing the environmental attitude. Thus, the psychographic peculiarities which inclined to greenness will induce better pro environmental attitude that ensure sustainability of environment. The study demonstrated that the psychographic characteristics has portrayed importance as determinants for the behavioural intention for environmentally safe products. This can help to elevate the comprehension of green practitioners for the psychographic factors influencing the purchase intention and decision. Better commitment can be demonstrated through comprehensive understanding of the consumers' requirement.